Combination of small interfering RNAs mediates greater inhibition of human hepatitis B virus replication and antigen expression - 陈喆 许则丰 叶景佳 姚航平 郑树 丁佳逸 (Journal of Zhejiang University. B. Science, 2005)
Objectives: To evaluate the inhibitory effect mediated by combination of small interfering RNAs (siRNAs) targeting different sites of hepatitis B virus (HBV) transcripts on the viral replication and antigen expression in vitro. Methods: (1) Seven siRNAs targeting surface (S), polymerase (P) or precore (PreC) region ofHBV genome were designed and chemically synthesized. (2) HBV-producing HepG2.2.15 cells were treated with or without siRNAs for 72 h. (3) HBsAg and HBeAg in the cell culture medium were detected by enzyme-linked immunoadsorbent assay. (4) Intracellular viral DNA was quantified by real-time PCR (Polymerase Chain Reaction). (5) HBV viral mRNA was reverse transcribed and quantified by real-time PCR. (6) The change of cell cycle and apoptosis was determined by flow cytometry. Results: Our data demonstrated that synthetic small interfering RNAs (siRNAs) targeting S and PreC gene could efficiently and specifically inhibit HBV replication and antigen expression. The expression of HBsAg and HBeAg and the replication of HBV could be specifically inhibited in a dose-dependent manner by siRNAs. Furthermore, our results showed that the combination of siRNAs targeting various regions could inhibit HBV replication and antigen expression in a more efficient way than the use of single siRNA at the same final concentration. No apoptotic change was observed in the cell after siRNA treatment. Conclusion: Our results demonstrated that siRNAs exerted robust and specific inhibition on HBV replication and antigen expression in a cell culture system and combination of siRNAs targeting different regions exhibited more potency.